Effect of Prenatal and Postnatal Exposure to an Aqueous Extract of Hibiscus sabdariffa (HS) on Postnatal Growth in Sprague-Dawley Rats - Iyare, E.E.; Iyare, F.E. (Pakistan Journal of Nutrition, 2008)
The present study was designed to investigate whether pups exposed to aqueous extract of HS during the foetal period and during early postnatal period would have a comparable growth with control pups in accordance with the "predictive adaptive response" hypothesis. Three groups of pregnant Sprague-Dawley (SD) rats were used for this study. Group C had tap water while groups A and B had 0.6g/100ml and 1.8g/100ml HS extract respectively to drink throughout pregnancy and through 20 days postpartum. All groups had normal rat chow ad libitum. Dam weights were recorded daily throughout pregnancy and through 20 days postpartum while pup weights were recorded at birth, 10 days, 14 days and 20 days postpartum. Results of the present study show no statistically significant difference (p>0.05) in the growth of pups at 10, 14 and 20 days postpartum in all groups except for group B pups whose growth was lower (p<0.05) at 20 days postpartum. We conclude that prenatal and early postnatal exposure to an aqueous extract of Hibiscus Sabdariffa does not appear to affect early postnatal growth in Sprague-Dawley rats.